Geometry of relativistic nuclei collision and hurst correlation curves - Fedosimova, A.I.; Lebedev, I.A.; Dmitrieva, E.A.; Bondar Е.А.; Olimov, H.K.; Ibraimova, S.A.; Mukanov, E.B. (Recent Contributions to Physics, 2023)
According to theoretical predictions, the mixed phase of "excited hadronic matter", including both free quarks and gluons, and protons with neutrons, should be formed in the energy range from 4 to 11 GeV per nucleon. Experiments performed with colliding beams have significant dead zones in which secondary particles and fragments of interacting nuclei are not detected. In this regard, there is not enough information about the initial state of the interaction. In this work, studies of the interaction of relativistic nuclei were carried out using a photoemulsion technique. This method (irradiation of a fixed target in a track detector) makes it possible to obtain the parameters of secondary particles and fragments of interacting nuclei in the entire spatial range. The analysis was carried out using experimental data obtained at the BNL synchrotron. NIKFI BR-2 emulsion plates, including light (HCNO) and heavy (AgBr) nuclei, were irradiated with a 197Au beam with an energy of 10.6 AGeV. In this work, we have jointly studied many-particle pseudorapidity correlations of secondary particles and fluctuations in the distributions of fragments of interacting nuclei based on event-by-event analysis to search for non-statistical clusters of secondary particles and taking into account the geometry of a nucleus-nucleus collision. To study correlations, we applied the method of correlation curves of Hurst. All events were divided into four types: uncorrelated, with jet-type correlations, with cluster-type correlations, and with mixed-type correlations. Events of different types differ significantly in the fragmentation of the projectile nucleus, the multiplicity of secondary particles, and the pseudorapidity distribution. Mixed-type events have an "anomalous" distribution of pseudorapidities: two groups of secondary particles are formed with significantly different pseudorapidities. The events mainly correspond to the central interactions of heavy Au nuclei with light CNO nuclei.